Pengaruh Dosis Pupuk Bokashi Gulma Air (Pistia stratiotes) dan Waktu Pemberian Terhadap Hasil Tanaman Pakcoy (Brassica rapa L.) - Makaruku, Marlta H; Samangun, Saverus; Polnaya, Fransin (JURNAL PERTANIAN KEPULAUAN, 2022)
Bokashi is a composting method that can use both aerobic and anaerobic starters to compost organic matter. The purpose of this study is to determine the correct dosage and time of application of water weed bokashi fertilizer (Pistia stratiotes), as well as obtaining its interaction with the yield of pakcoy plants (Brassica rapa L.). The research method using a Randomized Group Design (RAK) with two factors, namely the dose of water weed bokashi fertilizer (Pistia stratiotes) consists of 4 levels, namely: D0 = Dose of bokashi fertilizer 0 tons / ha (control), D1 = 10 tons / ha, D2 = 20 tons / ha, D3 = 30 tons / ha, and the time of application (W) consists of 3 levels, namely: W1 = 14 days before planting, W2 = 7 days before planting, W3 = same time of planting. Each combination of treatments is repeated 3 times. The size of the plot is 1 m × 1 m and in 1 plot there are 12 plants. The results showed that the dose treatment of water weed bokashi (Pistia stratiotes) was 20 tons / ha (D2), fertilizer application time 7 days before planting (W2) and its interactions had a very noticeable influence on all growth observation variables including plant height, number of leaves, leaf area.